Modélisation d’un module P V « « ECEN 2060 » » autonome sur Matlab - AMEUR, RACHID; BERRAHMOUNE, MOUNIR; GHEDEIR AMAR, AYOUB (université d'eloued, 2014)
The present work suggests how an optimal operation of a direct photovoltaic pumping system based on an induction motor can be achieved. The optimization problem consists in maximising the daily pumped water quantity via the minimisation of a non-linear criterion for any operating point. This has led to an optimum ‘ v-f ’ relationship useful in controlling the motor. The voltage source inverter feeding the motor was controlled via one of the following three PWM strategies called : the ‘sinusoidal PWM strategy’; the ‘Harmonic Elimination Technic’ or the ‘Harmonic Minimisation Technic’. The chosen optimisation criterion fixes the maximization of the motor efficiency or the power factor, since these two objective functions provides similar results. The extracted electric power is controlled by the inverter frequency instead of MPPT, which leads to a less expensive and non complex implementation. Thus the advantages described in are acquired mean while overriding their inconvenient. The obtained simulation results show that an increase of all the system performances such as the daily pumped quantity, the motor power factor and the pump efficiency are reached by the proposed approach when either the ‘sinusoidal PWM strategy’ or the ‘Harmonic Minimisation Technic’ is used. To illustrate the economic performance brought by the proposed approach, the irrigated area by this solar pumping system is calculated under sahara climate conditions for two crops. The pumped volume collected in the ten typical years and the irrigated area show well promising results.يقترح العمل الحالي كيفية التشغيل الأمثل للضخ الكهروضوئي المباشر يمكن تحقيق نظام يعتمد على المحرك التعريفي. مشكلة التحسين يتمثل في تعظيم كمية المياه التي يتم ضخها يوميًا عن طريق تقليل أ معيار غير خطي لأي نقطة تشغيل. وقد أدى هذا إلى "v-f" الأمثل علاقة مفيدة في السيطرة على المحرك. عاكس مصدر الجهد يغذي تم التحكم في المحرك عبر إحدى إستراتيجيات PWM الثلاثة التالية والتي تسمى: "استراتيجية PWM الجيبية"؛ "تقنية الحذف التوافقي" أو "التوافقي". تقنية التقليل. يعمل معيار التحسين المختار على إصلاح تعظيم كفاءة المحرك أو عامل القدرة، حيث توفر هاتين الوظيفتين الموضوعيتين نتائج مماثلة. يتم التحكم في الطاقة الكهربائية المستخرجة عن طريق تردد العاكس بدلاً من MPPT، مما يؤدي إلى تنفيذ أقل تكلفة وغير معقد. وبالتالي يتم الحصول على المزايا الموصوفة في المتوسط ​​مع تجاوزها غير مريح. تظهر نتائج المحاكاة التي تم الحصول عليها أن هناك زيادة في النظام بأكمله أداء مثل الكمية التي يتم ضخها يوميًا وعامل قوة المحرك و يتم الوصول إلى كفاءة المضخة من خلال النهج المقترح عند إما "الجيبية". يتم استخدام استراتيجية PWM أو تقنية التقليل التوافقي. لتوضيح الأداء الاقتصادي الناتج عن النهج المقترح، يتم حساب المساحة المروية بنظام الضخ الشمسي في ظل المناخ الصحراوي شروط لمحصولين. الحجم الذي تم ضخه تم جمعه في السنوات العشر النموذجية و وتظهر المنطقة المروية نتائج واعدة.
Catalogue d'Eléctromécanique Industrielleمذكرات ليسانس تخصص الكتروميكانيك
Keywords: Puissances maximales de lumière, énergies renouvelables, énergie solaire, MPPT; الاستطاعات الاعظمية للضوء,الطاقات المتجددة,الطاقة الشمسية,MPPT